Dynamic Capability-Based Mitigation of Displaced Commercial Risk in the Management of Temporary Syirkah Funds in Islamic Banks - Zakiyyah Ilma Ahmad; Ahmad Zainul Abidin; Maulana Zakaria Ahmad (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2026)
Background. This study presents an in-depth conceptual analysis of strategies for mitigating Displaced Commercial Risk (DCR), one of the most fundamental and distinctive risks faced by Islamic banks operating within a dual banking system. DCR refers to the situation in which Islamic banks are compelled to provide investment returns to depositors that do not accurately reflect the actual performance of the underlying assets in order to maintain market competitiveness. Aim. Consequently, this practice inherently undermines the fundamental principle of Profit and Loss Sharing (PLS) that distinguishes Islamic banking from conventional banking. Methods. Employing a qualitative conceptual approach through critical analysis and literature synthesis, this study deconstructs the limitations of the prevailing mitigation paradigm, which relies heavily on reactive instruments such as the Profit Equalization Reserve (PER). Results. As its primary contribution, this study proposes a Dynamic Capability Framework for DCR Mitigation. Rather than viewing DCR mitigation as a purely technical risk management function, the proposed framework conceptualizes it as a core organizational capability that Islamic banks must continuously develop and strengthen. The framework comprises three interrelated capability pillars: Sensing Capability, which identifies market volatility and asset-related risks; Seizing Capability, which responds proactively through effective Asset–Liability Management (ALM) and adaptive reserve management; and Transforming Capability, which enhances long-term organizational resilience through product innovation and stakeholder expectation management.